FROM FIELD TO MARKET: IMPROVING TRADE AND PRODUCING CHAINS IN UZBEKISTAN’S AGRO-CLUSTERS - Doniyor Abduazizov; Shoxrux Zulponov (Journals Park Publishing, 2024)
In modern entrepreneurship, the cluster approach serves as an effective tool for developing regional economies and increasing the competitiveness and innovative activity levels of organizations. The experience of economically advanced countries underscores the importance of clustering practices in the innovative development of the economy. This article examines the establishment and operation of agroclusters in Uzbekistan, particularly focusing on cotton clusters. By analyzing the current state and identifying key challenges such as insufficient trade relations, high export costs, lack of tax incentives, regulatory framework issues, and inadequate digitalization, this study highlights the critical areas needing improvement. Addressing these challenges is crucial for enhancing the efficiency and profitability of cotton clusters in Uzbekistan, thereby boosting their global competitiveness and contributing significantly to the country’s economic development.
Keywords: Agroclusters, trade relations, export costs, tax incentives, regulatory framework, digitalization, competitiveness, economic development.